Fermentation improves the potentiality of capsicum in decreasing high-fat diet-induced obesity in C57BL/6 mice by modulating lipid metabolism and hormone response. (October 2019) - Liu, Lu; Ding, Cheng; Tian, Min; Yi, Dongzheng; Wang, Jun; Zhao, Jinyue; Hu, Yong; Wang, Chao
Abstract: Capsicum has been proved to have anti-obesity effect. In this study, extracts from multi-strain coupled fermented capsicum (EFC) and from fresh capsicum (EC) were compared in their anti-obesity effect among these obese mice induced by high-fat diet (HFD), in order to exploring the potential mechanism of EFC for alleviating obesity. It has shown that the constituents of capsicum undergo transformation during fermentation. Obese mice in all experimental groups had similar energy absorption, and both EFC and EC relieved obesity, with better effect in the EFC group than in the EC group. Lower lipid and cholesterol were observed in serum, liver and feces in HFD-FC (HFD supplied with EFC)group compared to HFD-C (HFD supplied with EC) group. In addition, the HFD-FC group had less visceral fat and a smaller adipocyte size. The HFD-FC group exhibited better sensitivity to hormones, with lower levels of both leptin and insulin and higher ghrelin level. Expression of PPARα, CPT-1α, HSL and ACO were up-regulated, whereas PPARγ and C/EBPα were down-regulated significantly in the HFD-FC group compared to the HFD-C group. In summary, fermentation of Capsicum leads to a better effect on preventing fat accumulation and reducing lipid levels, which may be regulated by certain new contents in EFC that facilitate lipid metabolism and hormone response. Highlights: The consituents of capsicum undergo transformation during the fermentation. Fermention improves the effect of capsicum on relieving and preventing HFD-induced mouse obesity. Upon fermentation, capsicum improves the lipid metabolism and hormone response in obesity induced by HFD.